2016
DOI: 10.3390/ijerph13060623
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Attitudes toward Suicide and Family History of Suicide in Nagano Prefecture, Japan

Abstract: Certain attitudes toward suicide may be a risk factor for suicide among the bereaved. To explore this possibility, we examined the relationship between attitudes toward suicide and family history of suicide. We focused on two specific attitudes indicating resignation in a survey: #1 “When a person chooses to die by suicide, the suicide is inevitable” (i.e., inevitability belief); and #2 “A suicide cannot be stopped by any person, because suicide is unpreventable” (i.e., unpreventable belief). The data of 5117 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…Both quantitative and qualitative approaches have been used in the few studies attempting to explore attitudes to suicide after exposure to suicide. Some quantitative studies have used standardised attitudinal measures [ 39 41 ]. A population-based survey of 5117 Japanese adults bereaved by suicide compared with 2757 unexposed controls found that those bereaved by suicide were more likely to hold attitudes towards suicide as inevitable and not preventable [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both quantitative and qualitative approaches have been used in the few studies attempting to explore attitudes to suicide after exposure to suicide. Some quantitative studies have used standardised attitudinal measures [ 39 41 ]. A population-based survey of 5117 Japanese adults bereaved by suicide compared with 2757 unexposed controls found that those bereaved by suicide were more likely to hold attitudes towards suicide as inevitable and not preventable [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some quantitative studies have used standardised attitudinal measures [ 39 41 ]. A population-based survey of 5117 Japanese adults bereaved by suicide compared with 2757 unexposed controls found that those bereaved by suicide were more likely to hold attitudes towards suicide as inevitable and not preventable [ 39 ]. This must be interpreted in the context of the greater tolerance of suicide in Japanese culture [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, surveys in Norway and Australia found 18.9% and 11.5% of their respondents endorsed the misconception “Someone who is suicidal is determined to die” and “Once a person has made up his or her mind about suicide, no one can stop him or her,” respectively (Hjelmeland & Knizek, 2004; Nicholas et al, 2020); in contrast, our survey showed that 40.3% of the respondents agreed with a similar misconception “Someone who is suicidal is determined to die.” Furthermore, about half of our respondents endorsed the belief that “Talking about suicide would encourage suicide,” while a similar myth “There is a risk to evoke suicidal thoughts in a person’s mind if you ask about it” was endorsed by only 9.3% of the respondents in a survey from Norway (Hjelmeland & Knizek, 2004). In Japan, the prevalence of suicide misconceptions was quite low – only 9.8% of the respondents endorsed the statement that “When a person chooses to die by suicide, the suicide is inevitable,” and 16.4% agreed with the statement that “A suicide cannot be stopped by any person because suicide is unpreventable” (Tsukahara et al, 2016). It is possible that similar myths with different wordings might lead to different response patterns; for example, according to the survey in Australia, “Suicide happens without warning” and “Most suicides occur without any signs” were endorsed by 42% and 27% of the respondents, respectively (Nicholas et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We found that younger age groups had the highest prevalence rate of suicide misconceptions. Research from other countries, however, showed that older people were more likely to endorse suicide misconceptions (Nicholas et al, 2020;Till et al, 2018;Tsukahara et al, 2016). Although the underlying reasons for the relatively high prevalence of suicide misconceptions in Taiwanese younger generations are not known, this is worrisome as this may present a challenge for suicide prevention in this group.…”
Section: Sociodemographic Factors and Suicide Misconceptionsmentioning
confidence: 97%
“…This difference in emotional control strategies may impact on the willingness of Japanese bereaved to report symptoms of grief. Several researchers have noted ‘hidden grief,’ i.e., lack of reporting of grief distress, particularly after a death by suicide (Tsukahara et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%